Nucleotide exchange factor Rab3GEP requires DENN and non-DENN elements for activation and targeting of rab27a - Sanza, Paolo (2019)
Rab GTPases are compartment-specific molecular switches that regulate intracellular vesicular transport in eukaryotes. GDP/GTP exchange factors (GEFs) control Rab activation, and current models propose that localised and regulated GEF activity is important in targeting Rabs to specific membranes. Here, we investigated the mechanism of GEF function using the Rab27a GEF, Rab3GEP (also known as MADD), in melanocytes as a model. We show that Rab3GEP-deficient melanocytes (melan-R3G KO ) manifest partial disruption of melanosome dispersion, a read-out of Rab27a activation and targeting. Using rescue of melanosome dispersion in melan-R3G KO cells and effector pull-down approaches we show that the DENN domain of Rab3GEP (conserved among RabGEFs) is necessary, but insufficient, for its cellular function and GEF activity. Finally, using a mitochondrial re-targeting strategy, we show that Rab3GEP can target Rab27a to specific membranes in a GEF-dependent manner. We conclude that Rab3GEP facilitates the activation and targeting of Rab27a to specific membranes, but that it differs from other DENN-containing RabGEFs in requiring DENN and non-DENN elements for both of these activities and by lacking compartment-specific localisation.